2021
DOI: 10.48550/arxiv.2106.09506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-thermal electron energization during the impulsive phase of an X9.3 flare revealed by Insight-HXMT

P. Zhang,
W. Wang,
Y. Su
et al.

Abstract: The X9.3 flare SOL20170906T11:55 was observed by the CsI detector aboard the first Chinese Xray observatory Hard X-ray Modulation telescope (Insight-HXMT). By using wavelets method, we report about 22s quasiperiodic pulsations(QPPs) during the impulsive phase. And the spectra from 100 keV to 800 keV showed the evolution with the gamma-ray flux, of a power-law photon index from ∼ 1.8 before the peak, ∼ 2.0 around the flare peak, to ∼ 1.8 again. The gyrosynchrotron microwave spectral analysis reveals a 36.6 ± 0.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…In this study, we report the multi-periodic QPPs during the flare impulsive phase in Lyα, MUV Balmer continuum, low-frequency radio and HXR channels simultaneously. The short periods of 20−40 s are detected during ∼11:56−11:59 UT, which are similar to previous findings in the radio, HXR and γ-ray channels (Li et al 2020a;Zhang et al 2021). However, they could not study the QPP behaviors after 11:59 UT, largely due to their observational limitations.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, we report the multi-periodic QPPs during the flare impulsive phase in Lyα, MUV Balmer continuum, low-frequency radio and HXR channels simultaneously. The short periods of 20−40 s are detected during ∼11:56−11:59 UT, which are similar to previous findings in the radio, HXR and γ-ray channels (Li et al 2020a;Zhang et al 2021). However, they could not study the QPP behaviors after 11:59 UT, largely due to their observational limitations.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…They found that the QPP periods varied from around 12 s to 25 s in the thermal emission during the flare impulsive and decay phases, and attributed them to be the sausage oscillations of flaring loops. Next, Li et al (2020a) studied the flare-related QPPs with periods of about 20−30 s at channels of radio, HXR and γ-ray during the impulsive phase, and the similar periods were also reported by Zhang et al (2021). Then, Karlický & Rybák (2020) detected multiple periods (i.e., 1−2 s, 5.3−8.5 s and 11−30 s) mainly in the radio emission during the pre-impulsive and impulsive phases of the X9.3 flare.…”
Section: Summary and Discussionsupporting
confidence: 54%
See 3 more Smart Citations